A HfC-SiC multiphase ceramic matrix composite material and preparation method thereof
Through the method of combining HfC with SiC precursor reaction and PIP process, HfC-SiC composite ceramic matrix composite materials with high yield, excellent mechanical properties and oxidation resistance were prepared, which solved the high temperature in the preparation of existing HfC ceramic matrix composite materials. It deals with the problems of demand, low yield and poor oxidation resistance, and is suitable for ultra-high temperature environments.
Patent Information
- Application Number
- CN202211544338.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-04
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-12-04
AI Technical Summary
The existing HfC ceramic matrix composite preparation process has problems such as high-temperature treatment requirements, low ceramic yield, long preparation cycle, high cost and poor low-temperature oxidation resistance, which limits its application in ultra-high temperature environments.
The HfC-SiC composite ceramic precursor was prepared by reaction between the HfC precursor and the SiC precursor, and the precursor impregnation and cracking method (PIP) was used to combine chemical vapor deposition and high temperature treatment to prepare high ceramic yield, excellent mechanical properties and resistance. HfC-SiC composite ceramic matrix composite material with oxidation properties.
It improves ceramic yield, shortens the preparation cycle, improves the mechanical properties and oxidation resistance of the material, and is suitable for use in ultra-high temperature environments above 2000℃.
Smart Images

Figure CN115849910B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of ultra-high temperature ceramic-based composite materials, and in particular relates to a HfC-SiC multiphase ceramic-based composite material and a preparation method thereof. Background Art
[0002] HfC is an ultra-high temperature ceramic material with a high melting point (3890℃), good chemical stability and ultra-high temperature oxidation resistance. The ultra-high temperature ceramic-based composite material made by using it as a matrix and continuous carbon fiber reinforcement has a series of advantages such as low density, high strength, high fracture toughness, thermal shock resistance and ablation resistance. It can be used as a thermal structural component for a long time in an ultra-high temperature environment above 2000℃, and has broad application prospects in the field of hypersonic aircraft.
[0003] Precursor impregnation pyrolysis (PIP) is a commonly used method for preparing ultra-high temperature ceramic-based composite materials. It has the advantages of simple process equipment, low reaction temperature, short preparation cycle, and the ability to prepare parts with complex shapes and large sizes. However, since the liquid HfC precursor currently used in the PIP process needs to be treated at a temperature above 1500°C to obtain HfC ceramics, and the yield of the obtained ceramics is low (<50%), it generally requires more than 20 rounds of repeated impregnation-high temperature pyrolysis to obtain a composite material with a higher density, resulting in a long preparation cycle, high cost, and low performance of the composite material. In addition, the low-temperature oxidation resistance of a single HfC ceramic matrix is poor, which cannot meet the needs of thermal structural materials used under wide temperature conditions, limiting its wide application in the engineering field. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a HfC-SiC multiphase ceramic matrix composite material and a preparation method thereof. The present invention prepares a HfC-SiC multiphase ceramic precursor with a high ceramic yield by reacting a HfC precursor with a SiC precursor, and then prepares the HfC-SiC multiphase ceramic matrix composite material by a PIP process.
[0005] The method for preparing the HfC-SiC multiphase ceramic matrix composite material provided by the present invention comprises:
[0006] 1) reacting a SiC precursor with a HfC precursor shown in formula (I) to obtain a HfC-SiC composite ceramic precursor;
[0007]
[0008] R1 to R4 are all selected from at least one of a cyclopentadienyl group, a vinyl group and a C4-C8 alkyl group; and one of the groups R1 to R4 is a cyclopentadienyl group; the HfC precursor shown in formula I is an oxygen-free precursor and is liquid at room temperature (25°C);
[0009] 2) Using carbon fiber three-dimensional fabric as reinforcement to prepare a fabric preform;
[0010] 3) subjecting the fabric preform to high temperature pretreatment and chemical vapor deposition to obtain a fabric preform intermediate;
[0011] 4) impregnating, curing and low-temperature cracking the fabric preform intermediate obtained in step 3) in the HfC-SiC composite ceramic precursor obtained in step 1) to obtain a HfC-SiC composite ceramic matrix;
[0012] 5) Repeat step 4) to obtain a green body of the HfC-SiC multiphase ceramic matrix composite material;
[0013] 6) subjecting the HfC-SiC composite ceramic matrix composite material blank obtained in step 5) to high temperature treatment;
[0014] 7) Repeat step 4) and step 6) to obtain a HfC-SiC multiphase ceramic matrix composite material.
[0015] In step 1) of the above method, the SiC precursor is a mixture of solid polycarbosilane and liquid SiC precursor;
[0016] The mass ratio of the solid polycarbosilane to the liquid SiC precursor is (0.4-1.0):1; specifically 0.75-0.9:1;
[0017] The mass ratio of the SiC precursor to the HfC precursor shown in Formula I is 0.1-0.5:1, specifically 0.2:1.
[0018] In the step 1), the reaction temperature is 50-80°C, specifically 70°C, and the reaction time is 1-3h, specifically 2h.
[0019] In the step 2), the carbon fiber specification is T300-1K, T300-3K, T700-6K or T700-12K;
[0020] The fabric preform is fine-woven and punctured, carbon cloth laminated and stitched, needle-punched, needle-punched and stitched, orthogonal three-dimensional or three-dimensional five-dimensional;
[0021] Fabric density is 0.3g / cm 3 ~0.9g / cm 3 ; Specifically 0.6-0.85g / cm 3 or 0.8g / cm 3 .
[0022] In the step 3) of high temperature pretreatment, the temperature is 1100°C to 2500°C, specifically 1800°C, and the time is 1-2h, specifically 1.5h;
[0023] In the chemical vapor deposition step, the carbon source gas is propane or propylene;
[0024] The deposition temperature is 950-1100°C;
[0025] Vacuum degree is ≤200Pa;
[0026] The sedimentation weight gain rate is 10% to 80%, specifically 25-50%.
[0027] The chemical vapor deposition specifically includes: after the high-temperature pretreatment step, placing the fabric preform in a deposition furnace, evacuating the furnace to ≤200Pa, heating the furnace to the deposition temperature and keeping the temperature, introducing the carbon source gas for chemical vapor deposition, and depositing a cracked carbon layer of a certain thickness on the surface of the carbon fiber until the deposition weight gain rate meets the set value.
[0028] In the step 4), the immersion temperature is 50-80°C, specifically 70°C; the immersion pressure is -0.1MPa to 5.0MPa; the immersion pressure holding time is 1-3h, specifically 2h;
[0029] In the curing step, the holding time is 2 hours; the curing temperature is 150-240° C., specifically 200° C.; the curing time is 1-6 hours, specifically 4 hours;
[0030] In the low-temperature cracking step, the cracking temperature is 700°C to 1100°C, specifically 900°C, and the time is 1-4h, specifically 2h.
[0031] In the step 5), the number of repetitions is 3-5 times.
[0032] In the step 5) of high temperature treatment, the temperature is 1400° C. to 1600° C., specifically 1500° C., and the time is 1 hour.
[0033] The advantages of the present invention are:
[0034] (1) The HfC-SiC composite ceramic precursor has a high ceramic yield, wherein the 900°C ceramic yield is ≥60%;
[0035] (2) The ceramic component ratio obtained by high-temperature pyrolysis of the HfC-SiC composite ceramic precursor is adjustable, has good high-temperature stability, and part of the SiC matrix exists in the form of whiskers, which can greatly improve the mechanical properties of the material;
[0036] (3) The preparation cycle of HfC-SiC composite ceramic matrix composites is short, and dense composite materials can be obtained in 10-12 cycles;
[0037] (4) The material has excellent mechanical properties and anti-oxidation properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 TG curve of the HfC-SiC composite ceramic precursor prepared in Example 1;
[0039] Figure 2 This is the matrix morphology of HfC-SiC multiphase ceramic matrix composite material. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments. The methods are conventional methods unless otherwise specified. The raw materials can be obtained from public commercial channels unless otherwise specified. Obviously, the embodiments described are only part of the embodiments of the invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0041] The solid polycarbosilane, liquid SiC precursor and HfC precursor used are all commercially available. Solid polycarbosilane can be purchased from Suzhou Sailifei Ceramic Fiber Co., Ltd., Fujian Jianli Asia New Materials Co., Ltd., Ningbo Zhongxing New Materials Technology Co., Ltd.; liquid SiC precursor can be purchased from the Institute of Chemistry, Chinese Academy of Sciences; HfC precursor can be purchased from Fudan University.
[0042] Example 1
[0043] (1) Adding a SiC precursor to a liquid HfC precursor (R1 and R3 groups are cyclopentane, R2 and R4 are butane) as shown in formula I, stirring at 70° C. for 1 hour, reacting the precursors to obtain a HfC-SiC composite ceramic precursor; wherein the mass ratio of solid polycarbosilane to liquid SiC precursor is 0.9:1, and the mass ratio of SiC precursor to HfC precursor is 0.2:1.
[0044] (2) Using T300-1K carbon cloth laminated sutured structural fabric as reinforcement, a 200 mm × 200 mm fabric preform was prepared with a fabric density of 0.8 g / cm 3 .
[0045] (3) subjecting the fabric preform in (2) to high temperature pretreatment and chemical vapor deposition, wherein the high temperature pretreatment temperature is 1100° C. and the pretreatment time is 1 h;
[0046] After the high-temperature pretreatment step, the fabric preform is placed in a deposition furnace, evacuated to ≤200 Pa, heated to 950° C., and introduced with carbon source gas propane for chemical vapor deposition to deposit a certain thickness of cracked carbon layer on the surface of the carbon fiber until the deposition weight gain rate is 80%;
[0047] (4) The fabric preform after high-temperature pretreatment and chemical vapor deposition in (3) is impregnated with the HfC-SiC composite ceramic precursor in (1), the impregnation temperature is 70°C, the impregnation pressure is -0.1MPa~5.0MPa, and the impregnation pressure holding time is 2h. After the impregnation is completed, the blank is taken out and cured under the protection of an inert atmosphere. The curing temperature is 200°C and the curing time is 4h. It is then placed in a furnace and cracked at 900°C under the protection of an argon atmosphere. The holding time is 4h. The impregnation-curing-cracking steps are repeated for 3 rounds to obtain a HfC-SiC composite ceramic matrix composite blank with a certain density.
[0048] (5) The HfC-SiC composite material blank obtained in step (4) is subjected to high temperature treatment at 1400° C. for 1 h.
[0049] (6) After repeating step (4) and step (5) once, the impregnation-curing-cracking steps in step (4) are repeated for two rounds to finally obtain a dense C / HfC-SiC ceramic matrix composite material.
[0050] Figure 1 TG curve of the HfC-SiC composite ceramic precursor prepared in Example 1; it can be seen from the figure that the ceramic yield of the prepared HfC-SiC composite ceramic precursor at 900°C is greater than 60%, which is more than 20% higher than that of the HfC precursor.
[0051] Figure 2 The figure shows the matrix morphology of HfC-SiC composite ceramic matrix composite material. As can be seen from the figure, the matrix obtained by pyrolysis of the precursor contains SiC whiskers, which can greatly improve the mechanical properties of the material.
[0052] Finally, the density of the HfC-SiC composite ceramic matrix composite material obtained in this embodiment is 2.07 g / cm 3 , bending strength is 331MPa, fracture toughness is 15.1MPa·m 1 / 2 , the high temperature bending strength at 1800℃ is 359MPa.
[0053] Example 2
[0054] (1) A SiC precursor is added to a liquid HfC precursor (wherein R1 and R3 are vinylocene, and R2 and R4 are heptyl), and the mixture is stirred at 50°C for 3 hours to react the precursors to obtain a HfC-SiC composite ceramic precursor; wherein the mass ratio of solid polycarbosilane to liquid SiC precursor is 0.4:1, and the mass ratio of SiC precursor to HfC precursor is 0.5:1.
[0055] (2) Using T700-12K needle-punched sutured structural fabric as reinforcement, a 200 mm × 200 mm fabric preform was prepared with a fabric density of 0.6 g / cm 3 .
[0056] (3) subjecting the fabric preform in (2) to high temperature pretreatment and chemical vapor deposition, wherein the high temperature pretreatment temperature is 2500° C. and the pretreatment time is 2 h;
[0057] After the high-temperature pretreatment step, the fabric preform is placed in a deposition furnace, evacuated to ≤200 Pa, heated to 1000° C., and introduced with carbon source gas propylene for chemical vapor deposition to deposit a certain thickness of cracked carbon layer on the surface of the carbon fiber until the deposition weight gain rate is 50%;
[0058] (4) The fabric preform after high-temperature pretreatment and chemical vapor deposition in (3) is impregnated with the HfC-SiC composite ceramic precursor in (1), the impregnation temperature is 50°C, the impregnation pressure is -0.1MPa~5.0MPa, and the impregnation pressure holding time is 2h. After the impregnation is completed, the blank is taken out and cured under the protection of an inert atmosphere. The curing temperature is 240°C and the curing time is 1h. It is then placed in a furnace and cracked at 1100°C and under the protection of an argon atmosphere. The holding time is 1h. The impregnation-curing-cracking steps are repeated for 4 rounds to obtain a HfC-SiC composite ceramic matrix composite blank with a certain density.
[0059] (5) The HfC-SiC composite material blank obtained in step (4) is subjected to high temperature treatment at 1600° C. for 1 h.
[0060] (6) After repeating step (4) and step (5) once, the impregnation-curing-cracking steps in step (4) are repeated for two rounds to finally obtain a dense C / HfC-SiC ceramic matrix composite material.
[0061] Finally, the density of the HfC-SiC composite ceramic matrix composite material obtained in this embodiment is 2.11 g / cm 3 , bending strength is 347MPa, fracture toughness is 19.8MPa·m 1 / 2 , the high temperature bending strength at 1800℃ is 384MPa.
[0062] Example 3
[0063] (1) A SiC precursor is added to a liquid HfC precursor (wherein R1 and R3 are cyclopentyl groups, and R2 and R4 are hexyl groups), and the mixture is stirred at 70°C for 2 h to react with the precursors to obtain a HfC-SiC composite ceramic precursor; wherein the mass ratio of solid polycarbosilane to liquid SiC precursor is 0.75:1, and the mass ratio of SiC precursor to HfC precursor is 0.1:1.
[0064] (2) Using T300-3K fine-woven puncture structure fabric as reinforcement, a 200 mm × 200 mm fabric preform was prepared with a fabric density of 0.85 g / cm 3 .
[0065] (3) subjecting the fabric preform in (2) to high temperature pretreatment and chemical vapor deposition, wherein the high temperature pretreatment temperature is 1800° C. and the pretreatment time is 1.5 h;
[0066] After the high-temperature pretreatment step, the fabric preform is placed in a deposition furnace, evacuated to ≤200 Pa, heated to 1100° C., and introduced with carbon source gas propylene for chemical vapor deposition to deposit a certain thickness of cracked carbon layer on the surface of the carbon fiber until the deposition weight gain rate reaches 25%;
[0067] (4) The fabric preform after high-temperature pretreatment and chemical vapor deposition in (3) is impregnated with the HfC-SiC composite ceramic precursor in (1), the impregnation temperature is 70°C, the impregnation pressure is -0.1MPa~5.0MPa, and the impregnation pressure holding time is 2h. After the impregnation is completed, the blank is taken out and cured under the protection of an inert atmosphere. The curing temperature is 150°C and the curing time is 6h. It is then placed in a furnace and cracked at 700°C under the protection of an argon atmosphere. The holding time is 2h. The impregnation-curing-cracking steps are repeated for two rounds to obtain a HfC-SiC composite ceramic matrix composite blank with a certain density.
[0068] (5) The HfC-SiC composite material blank obtained in step (4) is subjected to high temperature treatment at 1500° C. for 1 h.
[0069] (6) After repeating step (4) and step (5) twice, the impregnation-curing-cracking steps in step (4) are repeated for two rounds to finally obtain a dense C / HfC-SiC ceramic matrix composite material.
[0070] Finally, the density of the HfC-SiC composite ceramic matrix composite material obtained in this embodiment is 2.03 g / cm 3 , bending strength is 323MPa, fracture toughness is 17.3MPa·m 1 / 2 , the high temperature bending strength at 1800℃ is 365MPa.
[0071] Although the specific embodiments and drawings of the present invention are disclosed for the purpose of illustration, the purpose is to help understand the specific contents of the present invention and implement them accordingly, it can be understood by those skilled in the art that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. The present invention should not be limited to the contents disclosed in the best embodiments and drawings of this specification, and the scope of protection claimed by the present invention shall be subject to the scope defined in the claims.
Claims
1. A method for preparing a HfC-SiC multiphase ceramic matrix composite material, comprising: 1) reacting a SiC precursor with a HfC precursor shown in formula (I) to obtain a HfC-SiC composite ceramic precursor; R1 to R4 are all selected from at least one of cyclopentadienyl, vinyl and C4-C8 alkyl; and one of the groups from R1 to R4 is cyclopentadienyl; In the step 1), the SiC precursor is a mixture of solid polycarbosilane and liquid SiC precursor; The mass ratio of the solid polycarbosilane to the liquid SiC precursor is (0.4-1.0):1; The mass ratio of the SiC precursor to the HfC precursor shown in formula I is 0.1 to 0.5:1; In the step 1), the temperature is 50-80°C and the reaction time is 1-3h; 2) Using carbon fiber three-dimensional fabric as reinforcement to prepare a fabric preform; In the step 2), the carbon fiber specification is T300-1K, T300-3K, T700-6K or T700-12K; The fabric preform is fine-woven and punctured, carbon cloth laminated and stitched, needle-punched, needle-punched and stitched, orthogonal three-dimensional or three-dimensional five-dimensional; Fabric density is 0.3g / cm 3 ~0.9g / cm 3 ; 3) subjecting the fabric preform to high temperature pretreatment and chemical vapor deposition to obtain a fabric preform intermediate; In the step 3) of high temperature pretreatment, the temperature is 1100°C to 2500°C and the time is 1-2h; In the chemical vapor deposition step, the carbon source gas is propane or propylene; The deposition temperature is 950-1100°C; Vacuum degree ≤200Pa; The sedimentation weight gain rate is 25% to 50%; The chemical vapor deposition comprises: after the high-temperature pretreatment step, placing the fabric preform in a deposition furnace, evacuating to ≤200 Pa, heating to the deposition temperature and keeping the temperature, introducing the carbon source gas for chemical vapor deposition, and depositing a cracked carbon layer of a certain thickness on the surface of the carbon fiber until the deposition weight gain rate meets the set value; 4) impregnating, curing and low-temperature cracking the fabric preform intermediate obtained in step 3) in the HfC-SiC composite ceramic precursor obtained in step 1) to obtain a HfC-SiC composite ceramic matrix; In the step 4), the immersion temperature is 50-80°C; the immersion pressure is -0.1MPa to 5.0MPa; and the immersion pressure holding time is 1-3h; In the curing step, the holding time is 2 hours; the curing temperature is 150-240° C.; and the curing time is 1-6 hours; In the low temperature cracking step, the cracking temperature is 700°C to 1100°C and the time is 1-4h; 5) Repeat step 4) to obtain a green body of the HfC-SiC multiphase ceramic matrix composite material; In the step 5), the number of repetitions is 3-5 times; 6) subjecting the HfC-SiC composite ceramic matrix composite material blank obtained in step 5) to high temperature treatment; In the high temperature treatment step, the temperature is 1400°C to 1600°C and the time is 1 hour; 7) Repeat step 4) and step 6) to obtain a HfC-SiC multiphase ceramic matrix composite material.
Citation Information
Patent Citations
Low-oxygen liquid SiHfBCN ceramic precursor, preparation method and SiHfBCN ceramic
CN111393579A